MR and CT Arthrography of the Shoulder - Rhee, Richard B.; Chan, Karence K.; Lieu, John G.; Kim, Brian S.; Steinbach, Lynne S. (Seminars in Musculoskeletal Radiology, 2012)
The combined use of shoulder arthrography with MR and CT imaging offers distinct advantages over conventional nonarthrographic imaging techniques. The improved contrast and joint distension afforded by direct arthrography optimize evaluation of various intra-articular structures and help to define subtle abnormalities and distinguish normal variants from true shoulder pathology. In this article, we review the rationale and basic approaches to shoulder arthrography as well as the imaging appearance of the normal shoulder, anatomical variants, and pathology highlighted by this technique.
Keywords: shoulder arthrography; MR arthrography; CT arthrography